2017
DOI: 10.1093/heapro/dax037
|View full text |Cite
|
Sign up to set email alerts
|

Australian employee perceptions of an organizational-level intervention to reduce sitting

Abstract: Stand Up Lendlease-a cluster-randomized trial targeting reductions in sitting time in Australian office workers (n = 153, 18 manager-led teams, 1 organization)-effectively reduced sitting time during work hours and across the day after 12 months. The trial included two arms: organizational-support strategies (e.g. manager support, emails) with or without an activity tracker. The current study aimed to examine participant perceptions of the intervention, and perceived barriers and facilitators for reducing sitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
5
24
1
1
Order By: Relevance
“…Consistent with previous research, agents citied various health and work-related benefits to reduced sitting at work, including reduced musculoskeletal symptoms [70], improved health awareness [64] and reduced fatigue [12]. Novel benefits perceived by agents included improved optical health, and improved tone of voice, confidence and assertiveness during customer calls while standing compared sitting.…”
Section: Discussionsupporting
confidence: 61%
“…Consistent with previous research, agents citied various health and work-related benefits to reduced sitting at work, including reduced musculoskeletal symptoms [70], improved health awareness [64] and reduced fatigue [12]. Novel benefits perceived by agents included improved optical health, and improved tone of voice, confidence and assertiveness during customer calls while standing compared sitting.…”
Section: Discussionsupporting
confidence: 61%
“…In addition to management support, previous studies have found workplace champions play an important role during the implementation of workplace interventions [21,23,[26][27][28][29]. However, in the present study, the role of ambassadors showed no relation to the effect of sitting, and interviews also listed mixed results.…”
Section: Organization Of the Interventioncontrasting
confidence: 83%
“…During the intervention period, participants were prompted to change their behaviour and e.g. raise their desks by seeing others doing so, and this is supported by findings from other sitting time interventions [ 27 , 30 32 ] and findings that workers in individual offices had higher sitting times compared to workers in shared offices [ 33 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The key adaption was the transfer of intervention implementation and evaluation from the research team to a workplace champion. This "train the champion" approach recognises that workplace champions, as the role models and drivers, are critical for successful and sustainable workplace change [11][12][13]. Notably, the translation of the Stand Up Australia intervention into a scalable and sustainable workplace health and safety program involves multiple phases [14].…”
Section: Introductionmentioning
confidence: 99%